The Influence of Sharia-Based Financial Planning and Self-Control on Succes of Students’ Financial Management - M. Satrya Mutthaqin; Ricca Hendarti; Mutiah Khaira Sihotang; Muslim Marpaung; Rahmanta Rahmanta (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
The rapid development of digital financial services has significantly influenced students’ financial behavior, often leading to increased consumptive tendencies without proper planning. This study aims to analyze the effect of sharia-Based financial planning and self-control on the Succes of Students’ Financial Management at the Faculty of Islamic Studies, Universitas Muhammadiyah Sumatera Utara. A quantitative approach with an explanatory survey design was employed, involving 93 students selected through proportional random sampling from a population of 1,364. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression with SPSS version 25. The results indicate that sharia-based financial planning has a positive and significant effect on Succes of Students’ Financial Management (t = 9.140; p < 0.05), and self-control also shows a positive and significant effect (t = 4.648; p < 0.05). Simultaneously, both variables significantly influence Succes of Students’ Financial Management (F = 205.205; p < 0.05), with a coefficient of determination (R²) of 0.820, indicating that 82% of the variation in Succes of Students’ Financial Management is explained by the model. These findings suggest that the integration of sharia-based financial planning and strong self-control plays a crucial role in improving students’ Succes of Students’ Financial Management. Sharia-based financial planning provides a structured and value-based framework, while self-control ensures consistent implementation in daily financial decisions. This study contributes to the development of Islamic financial behavior literature by highlighting the importance of combining cognitive and psychological factors in achieving financial well-being among students.